Drug dependence and drug abuse in the elderly from a gerontological perspective - Borazan, Nuran Gül; Kırışık, Hande; Ulusal, Furkan (Journal of Dependence, 2025)
As life expectancy increases, various health, psychological, and social problems specific to the elderly arise. Substance use, alcohol, or medications often emerge as commonly preferred solutions among the elderly as a way of coping with these challenges. Consequently, polypharmacy, or the use of multiple medications, is a frequently observed issue among older adults. It can be said that polypharmacy leads to different addictive behaviors in the elderly. This study evaluates the use of multiple medications, medication misuse, and medication addiction among the elderly from a gerontological perspective. Accordingly, it is crucial to carefully monitor the medication regimens of elderly individuals who are exposed to polypharmacy or long-term medication use. In collaboration with physicians and gerontologists, detailed information about the elderly’s illnesses, treatment processes, risks of polypharmacy, medication side effects, medication adherence, and follow-up should be provided, along with thorough education for both the patient and their relatives. This will help reduce the risk of addiction or misuse among elderly individuals. Gerontologists can conduct a holistic health assessment and closely monitor the effects of medications on the elderly in their home/institutional, family, and social life processes. Thus, in cooperation with gerontologists and physicians, the risk of medication misuse and addiction in the elderly can be minimized.